Order of entry and performance in international markets - Mascarenhas, Briance (Strategic Management Journal, 1992)
Abstract The inter‐market and intra‐market orders of entry and their performance consequences are examined for an industrial product. First entrants consist typically of both multinational and local firms, while early followers are multinational firms, and later entrants are smaller, local firms. A strong order of entry‐market share relationship is observed in international markets. First entrants and later entrants outsurvive early followers. The analysis reveals a strategy for achieving both first‐entry into many markets and dominance within those markets. Simultaneous entry into multiple markets occurs infrequently and in mature stages of the product life‐cycle.